Rheb-TOR signaling promotes protein synthesis, but not glucose or amino acid import, in Drosophila - de la Cruz Aida; Grewal Savraj S; Hall Dayna J; Edgar Bruce A (BMC Biology, 2007)
Abstract Background The Ras-related GTPase, Rheb, regulates the growth of animal cells. Genetic and biochemical tests place Rheb upstream of the target of rapamycin (TOR) protein kinase, and downstream of the tuberous sclerosis complex (TSC1/TSC2) and the insulin-signaling pathway. TOR activity is regulated by nutritional cues, suggesting that Rheb might either control, or respond to, nutrient availability. Results We show that Rheb and TOR do not promote the import of glucose, bulk amino acids, or arginine in Drosophila S2 cells, but that both gene products are important regulators of ribosome biogenesis, protein synthesis, and cell size. S2 cell size, protein synthesis, and glucose import were largely insensitive to manipulations of insulin signaling components, suggesting that cellular energy levels and TOR activity can be maintained through insulin/PI3K-independent mechanisms in S2 cell culture. In vivo in Drosophila larvae, however, we found that insulin signaling can regulate protein synthesis, and thus may affect TOR activity. Conclusion Rheb-TOR signaling controls S2 cell growth by promoting ribosome production and protein synthesis, but apparently not by direct effects on the import of amino acids or glucose. The effect of insulin signaling upon TOR activity varies according to cellular type and context.